Plan Colombia: rhetoric, reality, and the press - Delacour, Justin (Social justice, 2000)
Part of a special issue on neoliberalism, militarism, and armed conflict. The billion dollar aid package to Colombia agreed by the Senate in June 2000 is supposedly designed to fight the production and trafficking of illegal narcotics in Colombia, but the biggest beneficiary of the package is the Colombian army. This army has been associated with extensive human rights violations, and Plan Colombia was deeply opposed by human rights groups and many social and nongovernmental organizations in both countries. Furthermore, President Bill Clinton waived five of the six human rights conditions in the package in August 2000, basically making a mockery of the administration's declared concern for human rights.